Israel : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper analyzes the empirical relationship between corporate leverage-and other indicators of financial health-and investment in Israel, using dynamic panel data techniques. The results suggest that weak balance sheets may well have contributed to the investment decline of recent years. The impact of financial variables on investment is more pronounced for firms under financial pressure. However, there is little evidence that weak balance sheets' impact on corporate investment increases during real downturns or following an equity market bust.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet